The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3310/hta15150
|View full text |Cite
|
Sign up to set email alerts
|

Processes in recruitment to randomised controlled trials of medicines for children (RECRUIT): a qualitative study

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 168 publications
(232 reference statements)
3
94
0
Order By: Relevance
“…Initial reports from practices suggest that these gestures are appreciated and useful, primarily in introducing an element of "fun" to the recruitment process, but also helping to keep trial recruitment prominent within the practice. 5 Once participant recruitment to FiCTION is successfully completed we intend to evaluate the impact of the strategies developed from this survey on the overall process of recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial reports from practices suggest that these gestures are appreciated and useful, primarily in introducing an element of "fun" to the recruitment process, but also helping to keep trial recruitment prominent within the practice. 5 Once participant recruitment to FiCTION is successfully completed we intend to evaluate the impact of the strategies developed from this survey on the overall process of recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…4 The FiCTION trial involves the recruitment of children (aged 3 -7 years), which the RECRUIT study found to be even more challenging. 5 Additionally, these children are being recruited by more than 50 general dental practices across 5 regional centres over the UK. These general dental practices were already busy and few of them had participated in research before.…”
Section: Introductionmentioning
confidence: 99%
“…19 Parents were in the same room or an adjacent one when a child's interview was being conducted. Overall, children responded well to questions posed, but sometimes parents added comments to statements made or elaborated when a son or daughter struggled to verbalise his or her thoughts; this is something that others have noted to be helpful when gathering qualitative data from children.…”
Section: Qualitative Interviews With Parents and Children With Cleft mentioning
confidence: 99%
“…33,34 However, the fact that parents decide about participation for a child leads to a bioethical debate about whether or not one can act altruistically on behalf of another. 19 Parents may be concerned about making the 'right decision', seeing the need to protect their child from harm as fundamental. 35 As a consequence, although some studies have found that parents are motivated to consent to a trial for altruistic reasons, 36,37 it can be conditional on reassurances about concerns for a child's safety and well-being.…”
Section: Qualitative Interviews With Parents and Children With Cleft mentioning
confidence: 99%
See 1 more Smart Citation